2018
DOI: 10.1111/jac.12262
|View full text |Cite
|
Sign up to set email alerts
|

Root zone temperature alters storage root formation and growth of sweetpotato

Abstract: Large mounds amended with plant residues are a common cultivation method for sweetpotato (Ipomoea batatas) in the western parts of the Papua New Guinea highlands, with a suggested benefit of elevated root zone temperature (RZT) from decomposition. This study aimed to evaluate whether RZT affects the formation and growth of sweetpotato storage roots. Experiments evaluated the effects of a constant elevated RZT on the Beauregard cultivar and of a short‐term increase in RZT on the Beauregard and Northern Star cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
2
0
2
Order By: Relevance
“…At the early stage of high temperature, the leaf growth decreased, and at 5 d, some leaves began to fall off, possibly because the high temperature accelerated leaf senescence, resulting in leaf abscission. This study also indicated that the dry and fresh weights of the aboveground parts decreased significantly after high temperature stress ( Table 1 ), similar to the response of potato to high temperature ( Taranet et al., 2018 ). The effect of high temperature on the dry matter accumulation was related to its effect on the photosynthetic rate.…”
Section: Discussionsupporting
confidence: 72%
“…At the early stage of high temperature, the leaf growth decreased, and at 5 d, some leaves began to fall off, possibly because the high temperature accelerated leaf senescence, resulting in leaf abscission. This study also indicated that the dry and fresh weights of the aboveground parts decreased significantly after high temperature stress ( Table 1 ), similar to the response of potato to high temperature ( Taranet et al., 2018 ). The effect of high temperature on the dry matter accumulation was related to its effect on the photosynthetic rate.…”
Section: Discussionsupporting
confidence: 72%
“…Several studies have investigated the effects of different magnitudes and durations of suboptimal root temperature on plant growth and development. For example, a long-term elevated root temperature has a more pronounced effect on the storage root biomass of sweet potato (Ipomoea batatas) than a short-term increase in root temperature [36]. Transient root cooling at 14 • C for two weeks increased the shoot dry weight of commercial pepper compared to constant root cooling over six weeks [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, higher variations in day/nighttime temperatures significantly reduce the tuber yield by decreasing the activity of Rubisco, which controls the net photosynthesis (Meyers et al, 2017; Taranet et al, 2018; Wijewardana et al, 2018).…”
Section: Resilience Of Sweet Potato To Environmental Variables‐abioti...mentioning
confidence: 99%